AS3MT Polymorphism: A Risk Factor for Epilepsy Susceptibility and Adverse Drug Reactions to Valproic Acid and Oxcarbazepine Treatment in Children From South China - Fan, Xiaomei; Chen, Yuna; Lu, Jieluan; Li, Wenzhou; Li, Xi; Guo, Huijuan; Chen, Qing; Yang, Yanxia; Xia, Hanbing (Frontiers in Neuroscience, 2021)
Epilepsy is a common neurologic disorder characterized by intractable seizures, involving genetic factors. There is a need to develop reliable genetic markers to predict the risk of epilepsy and design effective therapies. Arsenite methyltransferase (AS3MT) catalyzes the biomethylation of arsenic and hence regulates arsenic metabolism. AS3MT variation has been linked to the progression of various diseases including schizophrenia and attention deficit or hyperactivity disorder. Whether genetic polymorphism of AS3MT contributes to epilepsy remains unclear. In this study, we investigated the association of AS3MT gene polymorphism with susceptibility to epilepsy in children from south China. We also explored the effect of AS3MT variation on the safety of antiepileptic drugs. Genotypic analysis for AS3MT rs7085104 was performed using samples from a Chinese cohort of 200 epileptic children and 244 healthy individuals. The results revealed a genetic association of AS3MT rs7085104 with susceptibility to pediatric epilepsy. Mutant homozygous GG genotype exhibited a lower susceptibility to childhood epilepsy than AA genotype. Carriers of AS3MT rs7085104 AA genotype exhibited a higher risk of digestive adverse drug reactions (dADRs) in children when treated with valproic acid (VPA) or oxcarbazepine (OXC). Additionally, bioinformatics analysis identified eight AS3MT target genes related to epilepsy and three AS3MT-associated genes in VPA-related dADRs. The effects of AS3MT on epilepsy might involve multiple targets including CNNM2, CACNB2, TRIM26, MTHFR, GSTM1, CYP17A1, NT5C2, and YBX3. This study reveals that AS3MT may be a new gene contributing to epileptogenesis. Hence, analysis of AS3MT polymorphisms will help to evaluate susceptibility to pediatric epilepsy and drug safety.